Roles of Integrins in Gastrointestinal Cancer Metastasis - Hou, Sicong; Wang, Jiaxin; Li, Wenqian; Hao, Xin; Hang, Qinglei (Frontiers in Molecular Biosciences, 2021)
Integrins are a large family of heterodimeric transmembrane receptors which mediate cell adhesion and transmit signals to the cell interior. The mechanistic roles of integrins have long been an enigma in cancer, given its complexity in regulating different cellular behaviors. Recently, however, increasing research is providing new insights into its function and the underlying mechanisms, which collectively include the influences of altered integrin expression on the aberrant signaling pathways and cancer progression. Many studies have also demonstrated the potentiality of integrins as therapeutic targets in cancer treatment. In this review, we have summarized these recent reports and put a particular emphasis on the dysregulated expression of integrins and how they regulate related signaling pathways to facilitate the metastatic progression of gastrointestinal cancer, including gastric cancer (GC) and colorectal cancer (CRC), which will address the crucial roles of integrins in gastrointestinal cancer.